Pengaruh Komposisi Media Dan Nutrisi Hidroponik Terhadap Pertumbuhan Dan Hasil Selada Hijau (Lactuca sativa Var.L) - Rika Agustina (Agrium, 2019)
The research conduct to hydroponic cultivation of lettuce plants with hydroponic media and nutrient composition to the growth and yield of lettuce. The research conducted at the Agro Wisata Hidroponik Meuria Paloh Muara Satu Subdistrict Lhokseumawe city. The activities started in April untill June 2019. This study aimed was determine the influence ofmedia and nutrient composition to the growth and yield of lattuce (Lactuca sativa Var. L).  This study used a Completely Randomized Design (CRD) factorial with 2 factors and 4 replications. The first factoris the provision of Nutrient (N) with 6 levels is: N1(6 ml AB Mix/ L), N2 (6 ml POC/L), N3 (6 ml Gandasil D/ L), N4 (3 ml AB Mix and 3 ml POC/L), N5 (3 ml AB Mix and 3 ml Gandasil D/L) dan N6 (3 ml POC and 3 ml Gandasil D/L). The second factor is the uses of planting media (M) with 2 M1 (rockwool) dan M2 (brick fragments). The result of this research showed that nutrients compotition and media hydroponics that treatment N4 and N5 give the better result of plant growth and yield mean while on the other hand and there is an interaction of fresh leaf weight. Keywords: AB Mix, POC NASA, Gandasil D,  Rockwool, Lettuce